Social science under debate : a philosophical perspective - Bunge, Mario, 1919-2020 (Book collections on Project MUSE., 1998)
Mario Bunge contends that social science research has fallen prey to a postmodern fascination with irrationalism and relativism. He urges social scientists to re-examine the philosophy and the methodology at the base of their discipline. Bunge calls for objective and relevant fact-finding, rigorous theorizing, and empirical testing, as well as morally sensitive and socially responsible policy design.